Penerapan Statistika dalam Meningkatkan Kualitas Penelitian Pendidikan - Pujiharti, Endang Sih (AN NAHDLIYYAH, 2026)
The proper application of statistics ensures that research is not only based on assumptions but also on concrete evidence, thus providing a basis for formulating educational policies. This research aims to identify and analyze how statistics can be used to improve the quality of educational research and significantly contribute to improving the overall quality of education. By using statistics, educators and researchers can identify educational problems, analyze data, and make more informed decisions to improve the quality of educational research. The appropriate and accurate application of statistics is key to improving the quality of educational research. By using statistics, researchers can analyze data more objectively, draw more valid conclusions, and make more informed decisions.